Palatal Rugae as an Indicator of Sexual Dimorphism - Dahal, Samarika; Baral, Radha; Gupta, Sanjay P; Dahal, Sirjana; Sharma, Rinu (Journal of Institute of Medicine Nepal, 2021)
Introduction Palatoscopy or palate rugoscopy has been studied over the years to identify its unique characteristics to utilize for the human identification process. The unique anatomical location of the palatal rugae provides stability which along with the uniqueness of the palatal rugae pattern can contribute in human identification. Despite its simplicity and reliability, the palatal rugae is unexplored in the Nepalese population. The objective of the present study is to identify the rugae pattern and assess its sexual dimorphism. Methods This is a cross-sectional analytical study conducted in Tribhuvan University Dental Teaching Hospital (TUDTH). The characteristics of palatal rugae based upon number, length, shape, and unification were analyzed on 100 dental casts. The rugae patterns were marked with a black color graphite pencil under adequate illumination. The length of the rugae was measured with the help of a digital vernier caliper and brass wire. The independent sample T-test and Mann Whitney U tests were used to assess the sexual dimorphism. Results The predominant type of rugae according to the size in both males and females was primary rugae. According to the shape of the rugae, the predominant type of rugae was wavy followed by curved, straight, diverging, converging, and circular in both the sexes. However, no significant difference was seen in the rugae pattern in males and females. Conclusion Based on the findings of the present study, the use of palatal rugae for sex determination is not recommended.